1999
DOI: 10.1063/1.478690
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular forces from density functional theory. III. A multiproperty analysis for the Ar(1S)-CO(1Σ) interaction

Abstract: The full anisotropic interaction between one Ar atom and the CO(1Σ) molecule treated as a rigid rotor (RR) at its equilibrium geometry is evaluated using density functional theory (DFT) to describe the short-range repulsive region (and its orientational anisotropy) as well as the well region and its angular dependence. The long-range dispersion forces are added from the results of perturbation theory and a scaling procedure is suggested for their correct matching with the DFT data. The computational results ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 37 publications
1
35
0
1
Order By: Relevance
“…A physically more reasonable procedure, used in this paper although far more elaborate in terms of computational cost, is to retain the r dependence of the IPES and subsequently perform the dynamical calculations using the appropriately averaged IPES and rotational constant for each CO vibrational state. The standard approach utilizing an inherently adiabatic IPES has been used in all but the latest theoretical investigation of the Ar-CO van der Waals complex in which Gianturco and Paesani, 31 by means of a semiempirical density functional theory-based scheme for calculating IPESs, 29 showed that the diabatic couplings due to the IPES are indeed negligible for bound state calculations in the three lowest vibrational states of CO.…”
Section: ͑4͒mentioning
confidence: 99%
See 3 more Smart Citations
“…A physically more reasonable procedure, used in this paper although far more elaborate in terms of computational cost, is to retain the r dependence of the IPES and subsequently perform the dynamical calculations using the appropriately averaged IPES and rotational constant for each CO vibrational state. The standard approach utilizing an inherently adiabatic IPES has been used in all but the latest theoretical investigation of the Ar-CO van der Waals complex in which Gianturco and Paesani, 31 by means of a semiempirical density functional theory-based scheme for calculating IPESs, 29 showed that the diabatic couplings due to the IPES are indeed negligible for bound state calculations in the three lowest vibrational states of CO.…”
Section: ͑4͒mentioning
confidence: 99%
“…29 A novel feature of this IPES is that the CO bond was allowed to relax upon complex formation. Subsequently, neglecting diabatic couplings, this three-dimensional IPES was averaged over the lowest vibrational states of the free CO molecule.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the M06-2X functional [102] is a highly non local functional with an enhanced contribution of non-local exchange completed with a meta-GGA correlation functional and was shown to provide reasonable results for noncovalent systems. In a more empirical scheme, the DFT energy can be corrected by an additional atom pair contribution to account for London dispersion through a −f (R)C 6 /R 6 term involving a short range cut-off f (R) [109][110][111][112][113][114][115][116]. ) and with the M06-2X functional [119].…”
Section: Treatment Of Long-range Interactions Within Dftmentioning
confidence: 99%